Employment convergence of immigrants in the European Union - Hámori, Szilvia (Hamburg, 2009)
"In light of the importance of immigrants’ labour market integration in the host countries, this study examines the employment convergence between foreign-born and native-born in the European Union (EU) based on the EU Labour Force Survey (EU LFS). The evidence points to numerous differences in assimilation patterns across immigrant groups (EU-born versus third country immigrants), genders and receiving EU regions. Potential explanations for these differences, such as the occupational composition of immigrants are discussed. Furthermore, predictions of the family investment hypothesis in terms of the human capital investment of the partners are tested in light of the finding that the employment rate of females born outside the EU exceeds that of similar native-born in the Southern EU member states."